Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557252
|View full text |Cite
|
Sign up to set email alerts
|

VacuumTouch

Abstract: We present VacuumTouch, a novel haptic interface architecture for touch screens that provides attractive force feedback to the user's finger. VacuumTouch consists of an air pump and solenoid air valves that connect to the surface of the touch screen and suck the air above the surface where the user's finger makes contact. VacuumTouch does not require the user to hold or attach additional devices to provide the attractive force, which allows for easy interaction with the surface. This paper introduces the imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similarly, Yamaoka et al reproduced the sensation of touching an adhesive surface by using the adhesive force of air suction (Yamaoka et al, 2008). In addition, Hachisu et al developed a table-top suction tactile presentation device and demonstrated that it is possible to modulate the sense of friction (Hachisu and Fukumoto, 2014).…”
Section: Suction-type Tactile Devicesmentioning
confidence: 99%
“…Similarly, Yamaoka et al reproduced the sensation of touching an adhesive surface by using the adhesive force of air suction (Yamaoka et al, 2008). In addition, Hachisu et al developed a table-top suction tactile presentation device and demonstrated that it is possible to modulate the sense of friction (Hachisu and Fukumoto, 2014).…”
Section: Suction-type Tactile Devicesmentioning
confidence: 99%
“…However, air jets can give users force feedback an a top-projected interactive surface by releasing compressed air through nozzles built into the surface (e.g., to impart force onto a handheld tool shaped like a cup) [35]. In the reverse direction air suction can provide force feedback through a perforated projection sheet through which a vacuum pump attracts the user's finger [14].…”
Section: Air Vertices and Air Suctionmentioning
confidence: 99%
“…For example, the touchpad-sized prototype can be turned into a top-projected display using a diffuser surface perforated at the location of the pins [14]. Alternatively, transparent electrodes can be placed on a diffuser surface for rear-projection [23], or on an LCD.…”
Section: Instrumentation For a Displaymentioning
confidence: 99%